Chromosome Level Genome Assembly and Annotation of Highly Invasive Japanese Stiltgrass (Microstegium vimineum). (28th October 2021) - Ramachandran, Dhanushya; Huebner, Cynthia D; Daly, Mark; Haimovitz, Jasmine; Swale, Thomas; Barrett, Craig F
Abstract: The invasive Japanese stiltgrass ( Microstegium vimineum ) affects a wide range of ecosystems and threatens biodiversity across the eastern USA. However, the mechanisms underlying rapid adaptation, plasticity, and epigenetics in the invasive range are largely unknown. We present a chromosome-level assembly for M. vimineum to investigate genome dynamics, evolution, adaptation, and the genomics of phenotypic plasticity. We generated a 1.12-Gb genome with scaffold N50 length of 53.44 Mb respectively, taking a de novo assembly approach that combined PacBio and Dovetail Genomics Omni-C sequencing. The assembly contains 23 pseudochromosomes, representing 99.96% of the genome. BUSCO assessment indicated that 80.3% of Poales gene groups are present in the assembly. The genome is predicted to contain 39, 604 protein-coding genes, of which 26, 288 are functionally annotated. Furthermore, 66.68% of the genome is repetitive, of which unclassified (35.63%) and long-terminal repeat (LTR) retrotransposons (26.90%) are predominant. Similar to other grasses, Gypsy (41.07%) and Copia (32%) are the most abundant LTR-retrotransposon families. The majority of LTR-retrotransposons are derived from a significant expansion in the past 1–2 Myr, suggesting the presence of relatively young LTR-retrotransposon lineages. We find corroborating evidence from Ks plots for a stiltgrass-specific duplication event, distinct from the more ancient grass-specific duplication event. The assembly and annotation of M. vimineum will serve as an essential genomic resource facilitating studies of the invasion process, the history and consequences of polyploidy in grasses, and provides a crucial tool for natural resource managers.